2022
DOI: 10.1128/iai.00001-22
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution of Antibiotic Tolerance in Patients with Persistent Methicillin-Resistant Staphylococcus aureus Bacteremia

Abstract: Severe infections caused by methicillin-resistant Staphylococcus aureus (MRSA) are often complicated by persistent bacteremia (PB) despite active antibiotic therapy. Antibiotic resistance rarely contributes to MRSA-PB, suggesting an important role for antibiotic tolerance pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Building on the recognition that adaptive evolution drives important clinical outcomes in S. aureus infections including both invasiveness of colonizing strains 137 , and persistence and treatment failure in invasive strains 130 , 143 , approaches to detect mutation in high-risk adaptive genes could support clinical decision making. This strategy has been successfully used in cancer medicine, whereby genomics approaches are used to detect driver mutations 169 .…”
Section: Immune Responses and Immune Evasion Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on the recognition that adaptive evolution drives important clinical outcomes in S. aureus infections including both invasiveness of colonizing strains 137 , and persistence and treatment failure in invasive strains 130 , 143 , approaches to detect mutation in high-risk adaptive genes could support clinical decision making. This strategy has been successfully used in cancer medicine, whereby genomics approaches are used to detect driver mutations 169 .…”
Section: Immune Responses and Immune Evasion Moleculesmentioning
confidence: 99%
“…Besides agr , there are other key core genes targeted by adaptive evolution that have regulatory functions: these include the essential cell-wall regulatory system walKR 24 , rsp (transcription factor repressor of surface proteins) 136 , 139 and the adaptor protein yjbH 130 , 140 , that interacts with the transcriptional regulator encoded by spx 141 . Recently, within-host genomic studies have also indicated that metabolic genes such as sucA - sucB are hotspots of bacterial host adaptation 130 , 142 , 143 . These adaptive processes seem to be specific to colonization and infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results so far suggest that because of its high penetrance antibiotic tolerance, is a much more effective means of drug survival than antibiotic persistence, which only allows the survival of a few bacteria. However, the flip side of tolerance is that it imposes a restricted growth rate to all cells in the population, which might explain why tolerance mutations were not commonly selected for following cyclical antibiotic exposure of several different bacterial pathogens [12,[26][27][28][29][30][31]. One hypothesis is that the fitness cost of tolerance mutations is too high in the absence of antibiotic treatment to be selected for over time.…”
Section: Tolerance and Persistence Have Different Fitness Trade-offs ...mentioning
confidence: 99%
“…In clinical settings, periodic rounds of antimicrobial therapy have been often associated with the appearance of hyper-persistence [26][27][28][29][30][31]. Interestingly, a hipA7 variant, the E. coli phenotypic equivalent of Salmonella shpAB1, was identified in patients with recurrent UTIs [31,36].…”
Section: Plos Pathogensmentioning
confidence: 99%